ФОРМИРОВАНИЕ ПОЗНАВАТЕЛЬНОЙ МОТИВАЦИИ В РАМКАХ ВЫСШЕГО ОБРАЗОВАНИЯ - USM ADMIN (Moldova State University, 2008)
In the given article questions of formation of cognitive motivation by means of problem methods of training at students within the limits of higher education are taken up. In given article attempt is undertaken to make definition concept problem training as the factor, promoting to stir up cogitative activity and as consequence to form cognitive motivation. Necessity of formation of cognitive motivation at students and introduction in process of training of the pedagogical model consisting of problems, questions and situations is proved.